Evaluation of a resorbable self‐locking ligation device for performing peripheral lung biopsies in a caprine cadaveric model. Issue 5 (25th January 2019) - Nylund, Adam M.; Chen, Chi‐Ya; Höglund, Odd V.; Campbell, Bonnie G.; Fransson, Boel A.
Abstract: Objective: To compare airway leak pressures after sealing peripheral lung biopsy sites with a resorbable ligation device (LigaTie) or thoracoabdominal (TA) staples. Study design: Ex vivo study. Animals: Four normal caprine cadavers. Methods: Twelve lung lobes were harvested from 4 goats immediately after euthanasia. Each lobe was inflated to 20 cm H2 O to test for leaks prior to biopsy. Pressure was then maintained at 10 cm H2 O. Biopsy samples were obtained 3 cm from the periphery with a resorbable ligation device or a TA stapler (n = 6 per group). After biopsy, inflation pressure was slowly increased to 40 cm H2 O while lungs were submerged in water. The pressure at which bubbles were first seen was recorded as the airway leak pressure. The length, width, volume, and weight were recorded for each biopsy sample. Results: Five of 6 LigaTie biopsy sites sustained the maximum pressure of 40 cm H2 O without leaking. One site leaked at 24 cm H2 O. The TA‐stapled sites sustained airway pressure to median 25.5 cm H2 O (interquartile range, 23.5–26 cm H2 O), and none of them reached the maximum pressure ( P  = .015). There were no differences in biopsy length, volume, or weight between groups. Conclusion: Biopsy sites sealed with LigaTie withstood higher airway pressure without leaking compared with TA‐stapled biopsy sites in normal cadaveric specimens. Clinical significance: The LigaTie may be an alternative technique for sealing peripheral lung biopsy sites.